Comparison Of Positive Law And Islamic Law In Registration Of Interfaith Marriage In Case Number 91/Pdt.P/2022/Pn Bks - Sihombing, Sastra Maidora; Heriamariaty, Heriamariaty; Susilowati, En (Journal of Law, Politic and Humanities, 2025)
This study looks at how interfaith marriage is controlled in Indonesia, with a focus on Decision Number 91/Pdt.P/2022/PN Bks. Interfaith marriages often create legal uncertainty, even though religion has a big impact on marriage law in Indonesia. Article 35letter a of the Population Administration Law, which allows marriage registration after a court ruling, was created to resolve this issue. The study aims to analyze the legal considerations behind the judge’s approval of interfaith marriage registration in this case. It also examines the legal status of such marriages from the perspectives of both positive law and religious law. The research uses a normative legal approach with narative-qualitative data analysis. The findings show that judges considered Article 35(a), human rights principles, non-discrimination, and relevant Supreme Court decisions in approving the request. However, under religious law, particularly Islamic law, such marriages are still considered invalid or haram, creating legal dualism. The problem is further complicated by the issuance of Supreme Court Circular Letter No. 2 of 2023, which restricts judicial discretion in similar future cases. This indicates that the challenge of harmonizing state law with religious norms continues and requires a more comprehensive legal solution. Keyword: Court Decision, Marriage Registration, Interfaith Marriage, Legal Dualism